Compendium Of Cardmaking Techniques (Tunbridge Wells, Kent Search Press, 2005)
There is something here to suit crafters of all abilities from paper crafts, embroidery and embossing to glass painting. Each project is clearly explained with simple step-by-step photography. The complete contents includes tea bag folding, iris folding, lacé, peel-offs, embroidery, punches, silk painting, glass painting, metal and wire, polymer clay, rubber stamping and embossing. Discover how to set a favourite photograph into a card, embroider a beautiful heart, paint a rose on silk, mould a mini wedding cake in polymer clay and fold tea bag papers into a delicate shapes. Be inspired to make innovative cards from all kinds of different materials!
This book provides a ready reference for the whole range of card making techniques including peel-off, rubber stamping, silk painting, embroidery, lace and iris folding. It includes designs for all occasions, including Valentine's Day, Christmas and New Baby
2 13 14
Keywords: Crafts & Hobbies; Greeting cards